Album of Girls' Boarding School, Mbereshi by Margaret Sabin
Groups include: staff and students, with later photographs of former students loose at the back of album. Photographs taken by/received from: Margaret Katherine Sabin. 1889 - 1978. [Served the LMS at Livingstone Memorial Girls' Boarding School, Mbereshi, Northern Rhodesia [now Zambia] 1926 - 1948.]